Electro-optic steering of Nematicons - Assanto, Gaetano; Piccardi, Armando; Barboza, Raouf; Alberucci, Alessandro (Photonics Letters of Poland, 2012)
We study the angular steering of spatial solitons in nematic liquid crystals, i.e. nematicons, exploiting their electro-optic response. Approaches to electro-optic steering include acting on the optic axis and walk-off, propagating the soliton through a voltage-adjusted refractive interface or getting it totally internally reflected. Using comb electrodes in a planar cell, maximum angular deflections of 70° are expected with the standard nematic liquid crystal mixture E7. Full Text: PDF References: I. C. Khoo , "Nonlinear optics of liquid crystalline materials", Phys. Rep. 471, 221 (2009).CrossRef M. Peccianti, G. Assanto, A. De Luca, C. Umeton, I.C. Khoo, "Electrically assisted self-confinement and waveguiding in planar nematic liquid crystal cells ", Appl. Phys. Lett. 77, 7 (2000).CrossRef M. Peccianti, and G. Assanto, "Signal readdressing by steering of spatial solitons in bulk nematic liquid crystals", Opt. Lett. 26, 1690 (2001)..CrossRef M. Peccianti, and G. Assanto, "Nematic liquid crystals: A suitable medium for self-confinement of coherent and incoherent light", Phys. Rev. E Rapid Commun. 65, 035603 (2002).CrossRef M. Peccianti, K.A. Brzdąkiewicz, and G. Assanto, , "Nonlocal spatial soliton interactions in nematic liquid crystals", Opt. Lett. 27, 1460 (2002).CrossRef M. Peccianti, G. Assanto, A. De Luca, C. Umeton, M. A. Karpierz, and I.C. Khoo, "Light Self-Confinement in Planar Cells with Nematic Liquid Crystals", J. Commun. Technol. Electron. 47, 790 (2002).CrossRef CrossRef G. Assanto, M. Peccianti, C. Conti, , "Spatial Optical Solitons in Bulk Nematic Liquid Crystals", Acta Phys. Pol. A 103, 161 (2003).CrossRef M. Peccianti, C. Conti, G. Assanto, A. De Luca, C. Umeton, , "Nonlocal Optical Propagation in Nonlinear Nematic Liquid CRrystals",J. Nonl. Opt. Phys. Mat. 12, 525 (2003).CrossRef G. Assanto, C. Conti and M. Peccianti, , "Highly Nonlocal Optical Solitons and Their Observation in Nematic Liquid Crystals", Int. Mod. Phys. Lett. B 18, 2819 (2004).CrossRef G. Assanto and M. Peccianti, "Guiding and Routing Light with Nematicons", Mol. Cryst. Liq. Cryst. 488, 163 (2008).CrossRef G. Assanto, M. Karpierz, "Nematicons: self-localised beams in nematic liquid crystals", Liq. Cryst. 36, 1161 (2009).CrossRef M. Peccianti, C. Conti, G. Assanto, A. De Luca, and C. Umeton, "Routing of anisotropic spatial solitons and modulational instability in liquid crystals", Nature 432, 733 (2004).CrossRef A. Alberucci, M. Peccianti, G. Assanto, G. Coschignano, A. De Luca, and C. Umeton,, "Self-healing generation of spatial solitons in liquid crystals", Opt. Lett. 30, 1381 (2005).CrossRef G. Assanto, C. Umeton, M. Peccianti, and A. Alberucci, "Nematicons and Their Angular Steering", J. Nonl. Opt. Phys. Mat. 15, 33 (2006).CrossRef M. Peccianti, A. Dyadyusha, M. Kaczmarek, and G. Assanto,, "Tunable refraction and reflection of self-confined light beams", Nat. Phys. 2, 737 (2006).CrossRef M. Peccianti, G. Assanto, A. Dyadyusha, and M. Kaczmarek, "Nonspecular Total Internal Reflection of Spatial Solitons at the Interface between Highly Birefringent Media", Phys. Rev. Lett. 98, 113902 (2007).CrossRef G. Assanto, and M. Peccianti, , "Routing light at Will", J. Nonl. Opt. Phys. Mat. 16, 37 (2007).CrossRef R. Barboza, A. Alberucci, and G. Assanto, , "Large electro-optic beam steering with nematicons", Opt. Lett. 36, 2611 (2011).CrossRef